Maternal over weight and obesity: its effect on pregnancy outcome. - Mazumder, U; Sarker, S; Riaz, BK; Chowdhury, TA (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 213-218 The abstract of this article is available on the PubMed website